2011
DOI: 10.1097/mat.0b013e31821f2296
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance and the Duration of the Hemodialysis Session

Abstract: Bioelectrical impedance analysis (BIA) is composed of resistance (R) and reactance (Xc). The aim of this study was to investigate whether BIA may be influenced by the duration of hemodialysis (HD) sessions. Eleven uremic patients underwent one 4-hour and one 8-hour bicarbonate HD session. Volume of blood and dialysate processed, volume of ultrafiltration (V(UF)), and dialysate electrolyte concentrations were prescribed to be the same. R and Xc were determined at the start and the end of each session, injecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This method may be replaced by a more elaborate method of segmental bioimpedance that may provide more exact data especially during the volume perturbation caused by UF. [33][34][35][36] Nevertheless, whole-body bioimpedance seems to be sufficient for studying the relations between Kr values and volume of body compartments in the clinical setting. However, more precise information about the change of fluid volume in different body segments would be interesting for further understanding of the refilling kinetics.…”
Section: Discussionmentioning
confidence: 98%
“…This method may be replaced by a more elaborate method of segmental bioimpedance that may provide more exact data especially during the volume perturbation caused by UF. [33][34][35][36] Nevertheless, whole-body bioimpedance seems to be sufficient for studying the relations between Kr values and volume of body compartments in the clinical setting. However, more precise information about the change of fluid volume in different body segments would be interesting for further understanding of the refilling kinetics.…”
Section: Discussionmentioning
confidence: 98%
“…This has potential clinical relevance, since maintenance of central blood volume is essential to maintain cardiac output and blood pressure. Basile et al (1) demonstrated intradialytic changes in whole body resistance using whole body bioimpedance at 50 kHz to be significantly greater in an 8-h dialysis treatment (at a low rate of ultrafiltration) than in a 4-h treatment (at a high rate of ultrafiltration) with the same ultrafiltration volume, presumably because relatively more fluid was removed from the leg in the longer dialysis treatment. Their paper provides evidence that change in whole body resistance during different dialysis durations and rate of ultrafiltration does not proportionally reflect fluid removal from the body.…”
Section: Intradialytic Change In Ecv Measured By Wbis and Sbismentioning
confidence: 99%
“…Therefore, knowledge of the effect of changes in fluid distribution occurring during the HD treatment on the accuracy of measurements is relevant. Whole body techniques assume that body segments (arm, trunk, and leg) can be modeled as a cylinder with uniform conductivity (1,19,20,26). However, the obvious differences in cross-sectional area between the trunk and limbs affect the accuracy of this method when nonphysiological changes in the distribution of ECV occur (20,28).…”
mentioning
confidence: 99%